Atmospheric transmission, emission and scattering - Kyle, Thomas G. ([S.l.] : Butterworth-Heinemann, 1991)
Introduces the physical processes and meteorology required to understand the behaviour of light and radiation in the atmosphere. Integrating the treatment of atmospheric optics from the ultraviolet to the microwave the book presents a detailed overview, together with discussions, on the associated meteorology and atmospheric composition, which gives the meteorological background necessary to deal with the varying conditions found in the real atmosphere. Mathematical details provide a concise description of results thus allowing readers with a knowledge of meteorology or a single wavelength region to comprehend the transmission, emission and scattering in all wavelength regions. Rayleigh and Mie scattering are covered as well as the aerosol and raindrop distributions found in the atmosphere. Detailed models of the atmosphere and the distribution of trace gases are supplied, and finally a chapter is devoted to standardised software and available data bases.
Keywords: atmospheric transmission,emission,scattering